2004
DOI: 10.1592/phco.24.8.750.36076
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in Patients' Potassium Concentrations During Spironolactone Therapy for Heart Failure

Abstract: Our findings suggest that a large percentage of patients with heart failure, particularly African-Americans, still require potassium supplementation despite treatment with spironolactone and standard vasodilator therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Our findings are consistent with 2 other analyses that also reported less pronounced changes in serum potassium in AA patients with HF who were taking spironolactone compared with non-AA patients. 10,11 Patients with HF may be at higher risk for hyperkalemia from renin-angiotensin-aldosterone system blockers because of inherently diminished renal perfusion, reducing delivery of sodium at distal tubule sites, which results in decreased potassium excretion.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with 2 other analyses that also reported less pronounced changes in serum potassium in AA patients with HF who were taking spironolactone compared with non-AA patients. 10,11 Patients with HF may be at higher risk for hyperkalemia from renin-angiotensin-aldosterone system blockers because of inherently diminished renal perfusion, reducing delivery of sodium at distal tubule sites, which results in decreased potassium excretion.…”
Section: Discussionmentioning
confidence: 99%
“…However, AAs had a significantly better response to eplerenone than to losartan (ARB), whereas no difference in response between these two agents was found in whites 88 . In patients with heart failure treated with spironolactone, AAs exhibit less hyperkalemia compared with whites when treated with MRAs 89 .…”
Section: Predictors Of Renin-angiotensin-aldosterone System Blockade mentioning
confidence: 96%
“…Short half-life is important to consider for safety concerns to yield a rapid decrease of active moieties when halting therapy in case of toxic side effects. Racial difference in response to MR blockade may exist: African Americans with heart failure are less responsive to the renal effect of spironolactone and develop less hyperkaliemia (Cavallari et al, 2004); this is not the case with eplerenone (Flack et al, 2003). It has been reported that spironolactone (at micromolar concentrations) inhibits aldosterone biosynthesis (Netchitailo et al, 1985) and blocks enzymes involved in steroidogenesis (Penhoat et al, 1988;Ye et al, 2009).…”
Section: A Steroidal Compoundsmentioning
confidence: 99%